P53 - the paradigm of tumor-suppresor genes? - Jezeršek Novaković, Barbara (Radiology and oncology (Ljubljana), 1998)
p53 is a tumor-suppressor gene the alterations of which are among the most frequent genetic changes detected in human neoplasms. Its product - p53 protein is a component of several biochemical pathways that are central to carcinogenesis: DNA transcription, genomic stability, DNA repair, cell cycle control, and apoptosis. The analysis of the spectrum of p53 mutations and insight into the p53 mediated biochemical pathways of programmed cell death and cell cycle arrest, provide clues to understanding of molecular pathogenesis of cancer of mechanisms related to p53 mediated tumor suppression. The purpose of the resent article is to summarise the most important facts concerning p53 since understanding of the above listed processes might provide the potential molecular targets for the development ofa rational cancer treatment.
Keywords: Genes, p53; Genes, suppressor, tumor; Genetics; geni; mutacije; Mutation; Neoplasms; Protein p53; rak (medicina); Transcription, genetic